2007
DOI: 10.1055/s-2007-984967
|View full text |Cite
|
Sign up to set email alerts
|

Kurzfassung der aktualisierten S3-Leitlinie „Diagnostik und Therapie der Hepatitis B”

Abstract: Therapeutic option for hepatitis B virus infection have significantly improved in recent years. Moreover, new insights in the natural history of hepatitis B required an update of current national guidelines. Therefore, the German network of competence on viral hepatitis (Hep-Net) has revised guidelines on diagnosis and treatment og HBV incetion in cooperation with the national societies for Gastroenterology, Pathology, Virology, and Pediatric Gastroenterology. Important alterations concern the indication for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Several studies have shown that chronic HDV infection leads to more severe liver disease than chronic HBV mono-infection, with an accelerated course of progression to fibrosis, increased risk of HCC and early decompensation of cirrhosis (28,(33)(34)(35)(36)(37). HDV accounts for almost half of all cases of cirrhosis and HCC in South-East Turkey (34,38,39).…”
Section: Natural History Of Chronic Hepatitis Dmentioning
confidence: 99%
“…Several studies have shown that chronic HDV infection leads to more severe liver disease than chronic HBV mono-infection, with an accelerated course of progression to fibrosis, increased risk of HCC and early decompensation of cirrhosis (28,(33)(34)(35)(36)(37). HDV accounts for almost half of all cases of cirrhosis and HCC in South-East Turkey (34,38,39).…”
Section: Natural History Of Chronic Hepatitis Dmentioning
confidence: 99%